The Role of the Communication Climate, Appearance Attraction and Personality Type to the Silence Behaviour of the Malays in the German Multinational Company - Yusuf, Robe'ah; Mohd Rosdi, Siti Asma'; Moneyam, Sasigaran; Ramdan, Mohamad Rohieszan; Yani, Achmad (Journal of Humanities and Social Sciences (JHASS), 2023)
Silence behaviour is a phenomenon that occurs in an organisation that is influenced by various factors. The behaviour of employees who fail to provide important information to the immediate superior is influenced by related factors such as communication climate, appearance attraction and personality type (extrovert-introvert). This study examined the influence of the communication climate, appearance attraction and personality type (introverted extroverts) on silence behaviour. PLS-SEM is used to test the hypothesis based on data from 360 Malay workers in four key sectors: industry, services, banking, and education, especially in the Klang Valley. The findings showed a significant positive direct relationship between communication climate, appearance attraction, personality type (extrovert-introverted), and silence behaviour. Theoretically, this study contributes to the knowledge management literature by studying the communication climate, appearance attraction and personality of introverted extroverts, which has proven that predictors of silence behaviour directly. Meanwhile, the application practically helps the management to identify the behaviour of Malay employees by promoting holistic dissemination of information within the organisation.